2005
DOI: 10.1021/es049772b
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Characterization of Four “Asian Dust” Samples Collected in Korea, Using Low-Z Particle Electron Probe X-ray Microanalysis

Abstract: A single-particle analytical technique, named low-Z particle electron probe X-ray microanalysis (low-Z particle EPMA), employing an ultrathin window X-ray detector and enabling the quantitative determination of even low-Z elements such as C, N, and O, is applied to characterize "Asian Dust" samples, collected in ChunCheon, Korea, during four Asian Dust storm events on March 7, 2000, April 7, 2000, March 22, 2001, and May 17, 2001. In this study, it is demonstrated that single-particle analysis using the low-Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 35 publications
4
91
0
1
Order By: Relevance
“…As presented in Table 2, the ratios range from 0.39 to 0.87, indicating that the remaining carbonate fractions in the dust particles range from 39-87%, respectively, even after the chemical aging times of 24-84 hrs. Several single particle chemical analysis studies with East Asian dust particles reached the same conclusions (Ro et al, 2005;Zhang et al, 2003;Zhang and Iwasaka, 1999). The replaced CO 3 2-fractions of 13-61% are believed to be released from dust particles by nitrate (and/ Surface roughness factor; 3) Values recommended by this study.…”
Section: Research and Theoretical Backgroundsupporting
confidence: 76%
See 1 more Smart Citation
“…As presented in Table 2, the ratios range from 0.39 to 0.87, indicating that the remaining carbonate fractions in the dust particles range from 39-87%, respectively, even after the chemical aging times of 24-84 hrs. Several single particle chemical analysis studies with East Asian dust particles reached the same conclusions (Ro et al, 2005;Zhang et al, 2003;Zhang and Iwasaka, 1999). The replaced CO 3 2-fractions of 13-61% are believed to be released from dust particles by nitrate (and/ Surface roughness factor; 3) Values recommended by this study.…”
Section: Research and Theoretical Backgroundsupporting
confidence: 76%
“…HNO 3 levels of 1-3 ppb were frequently observed with high dust concentrations over the downwind areas from the polluted regions in East Asia (this will be discussed in more detail in section 2.4; also refer to Bauer et al (2004)). However, such large amounts of nitrate have never been found in dust particles, particularly in East Asia (Song et al, 2007;Ro et al, 2005;Song et al, 2005;Zhang et al, 2003). In contrast, when γ HNO 3 = = 10 -3 -10 -5 , R HNO 3 become much slower (τ 10 =3.1-91.8 days).…”
Section: Reaction Probability Of Hno 3 (γ γ Hno 3 )mentioning
confidence: 99%
“…The net X-ray counts (= total counts -carbon-Formvar blank counts) of elements for each particle analysed were calculated, and their proportions were normalized to 100%. Although the elemental results were semiquantitative, the accuracy is sufficient to identify different particle types and to compare the differences in elemental ratios of the same particle type in different samples (Pósfai et al, 2003;Ebert et al, 2004;Niemi et al, 2005b;Ro et al, 2005;Laskin et al, 2006). The strong vacuum (∼10 −7 torr) and beam exposure causes evaporation of semivolatile compounds from particles, and for that reason, water, ammonium nitrate and organic compounds with high vapour pressure were lost, as is typical in electron microscopy.…”
Section: Tem/edx Individual Particle Analysesmentioning
confidence: 99%
“…Ro et al (2005) reported components such as MgCO 3 , MgSO 4 , K 2 CO 3 , KNO 3 , and K 2 SO 4 in single-particle measurements of Asian dust sampled in Korea. The nitrate and sulfate components may have formed during transport via heterogeneous reactions with carbonates.…”
Section: Introductionmentioning
confidence: 99%